The Role of Iron and Nerve Inflammation in Diabetes Mellitus Type 2-Induced Peripheral Neuropathy. (15th May 2019) - Paeschke, Sabine; Baum, Petra; Toyka, Klaus V.; Blüher, Matthias; Koj, Severin; Klöting, Nora; Bechmann, Ingo; Thiery, Joachim; Kosacka, Joanna; Nowicki, Marcin
Abstract: Peripheral diabetic neuropathy (PDN) is one of the most common complications of diabetes mellitus. Previous studies showed an association between dietary iron load and inflammation in the development of PDN in a rat model of type 1 diabetes (T1D). Here we investigated the role of iron and neural inflammation in development of PDN in a animal model of obesity and type 2 diabetes (T2D). 3-month-old db/db mice were fed with a high, standard or low iron diet for 4 months. High iron chow lead to a significant increase in motor nerve conduction velocities compared to mice on standard and low iron chow. Direct beneficiary effects on lowering blood glucose and HbA1c concentrations were shown in the high iron treated diabetic mice. Numbers of pro-inflammatory M1 macrophages were reduced in nerve sections, and anti-inflammatory M2 macrophages were increased in db/db mice on high iron diet compared to other groups. These results confirm and extend our previous findings in STZ-diabetic rats by showing that dietary non-hem iron supplementation may partly prevent the development of PDN in opposition to iron restriction. The identification of these dietary iron effects on the metabolic and inflammatory mechanisms of PDN supports a role of dietary iron and leads us to suggest testing for iron levels in human diabetic patients. Highlights: MNCV increased in high iron db/db mice compared to the other db/db groups. M1 macrophages were decreased and M2 macrophages increased in high iron db/db mice. Blood glucose and HbA1c levels were reduced in high iron db/db group.